Macrophage Differentiation in Normal and Accelerated Wound Healing - Kotwal, Girish J. (Results Probl Cell Differ, 2017)
Chronic wounds pose considerable public health challenges and burden. Wound healing is known to require the participation of macrophages, but mechanisms remain unclear. The M1 phenotype macrophages have a known scavenger function, but they also play multiple roles in tissue repair and regeneration when they transition to an M2 phenotype. Macrophage precursors (mononuclear cells/monocytes) follow the influx of PMN neutrophils into a wound during the natural wound-healing process, to become the major cells in the wound. Natural wound-healing process is a four-phase progression consisting of hemostasis, inflammation, proliferation, and remodeling. A lag phase of 3–6 days precedes the remodeling phase, which is characterized by fibroblast activation and finally collagen production. This normal wound-healing process can be accelerated by the intracellular delivery of ATP to wound tissue. This novel ATP-mediated acceleration arises due to an alternative activation of the M1 to M2 transition (macrophage polarization), a central and critical feature of the wound-healing process. This response is also characterized by an early increased release of pro-inflammatory cytokines (TNF, IL-1 beta, IL-6), a chemokine (MCP-1), an activation of purinergic receptors (a family of plasma membrane receptors found in almost all mammalian cells), and an increased production of platelets and platelet microparticles. These factors trigger a massive influx of macrophages, as well as in situ proliferation of the resident macrophages and increased synthesis of VEGFs. These responses are followed, in turn, by rapid neovascularization and collagen production by the macrophages, resulting in wound covering with granulation tissue within 24 h.